Immersion, interaction, and experience-oriented learning: Bringing virtual reality into FL learning - Lan, Yu-Ju (Language learning & technology, 2020)
Virtual reality (VR) is not only attracting the attention of the information and computer technology (ICT) industry (Shirer & Torchia, 2017), especially in the production of consumer VR hardware, but also that of educators. One of the important features of VR is immersion, which enhances the situated experience of users. The sensation of being there no longer necessitates a physical presence (Flower, 2015). This aspect allows second language (L2) and foreign language (FL) learners to combine learning an additional language with an intercultural experience beyond geographical limitations with no need to step out of the classroom or leave their home countries (Wang, Petrina, & Feng, 2017). Another important feature supported by VR applications is interaction, which provides users with a special channel of interpersonal communication (Ip et al., 2016). Given the importance of situated and contextual learning to FL learning, the specific features of VR of immersion and interaction are also of great interest to language educators. This article reviews previous studies of the application of VR for FL learning, introduces the present-day advanced developments in VR technology that have considerable potential for FL learning, and describes the research trends of VR in this area.